2018
DOI: 10.21037/jtd.2017.10.03
|View full text |Cite
|
Sign up to set email alerts
|

The influence of less invasive ventricular assist device implantation on renal function

Abstract: LVAD implantation improves kidney function in patients with renal dysfunction. A considerable difference in the change of renal parameters was detected in patients with LIS as compared to SAS, which was not significant possibly due to the limited size of the patient cohort (n=13).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Therefore, the higher eGFR values in the LVAD group compared with the non-LVAD group at the time of waitlisting can reliably be explained by an LVAD-induced increase in eGFR values. Similar results have been reported by others [ 21 23 ]. Moreover, earlier studies also provided evidence that the increase in eGFR after LVAD implantation may be transient, but long-term data were limited.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the higher eGFR values in the LVAD group compared with the non-LVAD group at the time of waitlisting can reliably be explained by an LVAD-induced increase in eGFR values. Similar results have been reported by others [ 21 23 ]. Moreover, earlier studies also provided evidence that the increase in eGFR after LVAD implantation may be transient, but long-term data were limited.…”
Section: Discussionsupporting
confidence: 93%
“…Schmitto et al were the first to describe a minimally approach for LVAD implantation (6,9) using a left mini-thoracotomy and a J-shaped hemisternotomy (6,9). This less invasive technique for LVAD implantation is increasingly used worldwide, and there is now growing evidence of its benefits compared to the full sternotomy approach (10)(11)(12)(13)(14)(15). These studies have demonstrated the feasibility of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Some demonstrated benefits to this approach have been decreased bleeding, improved renal function, and decreased right heart dysfunction. [32][33][34] . Most recently, the HeartWare Lateral Trial was reported.…”
Section: Minimally Invasive Left Ventricular Assist Device Placementmentioning
confidence: 99%